Karakteristik gel aromaterapi pengharum ruangan dari karagenan-glukomanan dengan minyak atsiri serai wangi dan jeruk kalamansi sebagai pewangi - Winda Nur’aini; Devi Silsia; Syafnil yafnil (AGROINTEK, 2024)
Citronella essential oil and calamansi orange essential oil can cause a relaxing effect, so it can be used as a fragrance in the aromatherapy gel to make room freshener. This study aimed to determine the effect of the addition of citronella oil and calamansi citrus on the characteristics of the resulting air freshener aromatherapy gel and the most preferred gel formula. This study used a complete randomized design (CRD) with One factor: the ratio of essential oil of citronella and citrus calamansi. The ratio of essential oils of citronella and citrus calamansi used (%) were 0:100, 30:70, 40:60, 50:50, 60:40, 70:30, 100:0. The results showed that the addition of essential oils of citronella and citrus calamansi had a significant effect on syneresis, evaporation of liquid substances and the residual weight of aromatherapy gels, but had insignificant effect on color, gel and hedonic fragrance resistance. The gel syneresis value and residual weight get higher at more concentrations of citronella essential oil but provide a low total value of liquid evaporation. The most preferred air freshening aromatherapy gel was on the use of 100% calamansi orange essential oil. Panelists liked the whiter color of the gel, preferred the citrus scent, and the texture that didn't crumble easily.